2010
DOI: 10.1093/brain/awq069
|View full text |Cite
|
Sign up to set email alerts
|

Powerful beneficial effects of benfotiamine on cognitive impairment and  -amyloid deposition in amyloid precursor protein/presenilin-1 transgenic mice

Abstract: Reduction of glucose metabolism in brain is one of the main features of Alzheimer's disease. Thiamine (vitamin B1)-dependent processes are critical in glucose metabolism and have been found to be impaired in brains from patients with Alzheimer's disease. However, thiamine treatment exerts little beneficial effect in these patients. Here, we tested the effect of benfotiamine, a thiamine derivative with better bioavailability than thiamine, on cognitive impairment and pathology alterations in a mouse model of Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
133
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(149 citation statements)
references
References 36 publications
13
133
0
3
Order By: Relevance
“…Here, we present the results of a clinical case study showing the potential of benfotiamine as a disease-modifying drug for AD. As a derivative of thiamine with better bioavailability, benfotiamine has been demonstrated to exert beneficial effects against abnormal glucose metabolism and its consequences via multiple mechanisms, including the elimination of oxidative stress [16,17] and the inhibition of glycogen synthase kinase-3 [18], which are both considered to be major pathogenic factors that cause neurodegeneration in AD. The better bioavailability and the pharmacological effects via multiple mechanisms against abnormal glucose metabolism and its consequences may explain why benfotiamine administration but not thiamine supplementation [24] had a long-term beneficial effect on cognitive ability in AD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we present the results of a clinical case study showing the potential of benfotiamine as a disease-modifying drug for AD. As a derivative of thiamine with better bioavailability, benfotiamine has been demonstrated to exert beneficial effects against abnormal glucose metabolism and its consequences via multiple mechanisms, including the elimination of oxidative stress [16,17] and the inhibition of glycogen synthase kinase-3 [18], which are both considered to be major pathogenic factors that cause neurodegeneration in AD. The better bioavailability and the pharmacological effects via multiple mechanisms against abnormal glucose metabolism and its consequences may explain why benfotiamine administration but not thiamine supplementation [24] had a long-term beneficial effect on cognitive ability in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that benfotiamine improves cognitive impairment in a mouse model of AD (amyloid precursor protein/presenilin-1 (APP/PS1) transgenic mice) [18]. Here, we investigated the effects of benfotiamine on the cognitive ability and amyloid accumulation in the brain assayed by positron emission tomography with Pittsburgh compound-B (PiB-PET) in five patients with mild to moderate AD.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…All female APP/PS1 transgenic mice (4.5 months old) with a confirmed genotype were produced by the Model Animal Research Center of Nanjing University (Pan et al ., 2010). Female transgenic mice were used because female mice manifest an early deficit in spatial memory in the MWM test and develop greater Aβ burden compared to age‐matched male mice (Gallagher et al ., 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The levels of thiamine, TMP, and TDP were measured using HPLC as previously described in detail [18] . Briefl y, 150 μL of 7.4% perchloric acid was immediately added to 150 Apolipoprotein E Genotype Analysis APOE alleles were detected using the ABI real-time Taqman SNP genotyping assay (L ife Technologies, Carlsbad, CA) according to the manufacturer's instructions.…”
Section: Determination Of Thiamine Tmp and Tdp Levelsmentioning
confidence: 99%